2020
DOI: 10.1002/hep.31221
|View full text |Cite
|
Sign up to set email alerts
|

miR‐210 Participates in Hepatic Ischemia Reperfusion Injury by Forming a Negative Feedback Loop With SMAD4

Abstract: Background and Aims Hepatic ischemia‐reperfusion (IR) injury is a major complication of liver transplantation, resection, and hemorrhagic shock. Hypoxia is a key pathological event associated with IR injury. MicroRNA‐210 (miR‐210) has been characterized as a micromanager of hypoxia pathway. However, its function and mechanism in hepatic IR injury is unknown. Approach and Results In this study, we found miR‐210 was induced in liver tissues from patients subjected to IR‐related surgeries. In a murine model of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In addition, we also found four regulatory loops, including Fosl2-miR-155-Fosl2, Fosl2-miR-146a-Fosl2, Cebpb-miR-155-Cebpb and Mafk-miR-25-Mafk. Regulatory loop has been reported in liver ischemia-reperfusion injury ( Pan et al, 2020 ). Our results showed that transcription factors bind to the promoter of miRNA and induce miRNA express, so as to form a negative feedback loop with TF and maintain the stability of their expression level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found four regulatory loops, including Fosl2-miR-155-Fosl2, Fosl2-miR-146a-Fosl2, Cebpb-miR-155-Cebpb and Mafk-miR-25-Mafk. Regulatory loop has been reported in liver ischemia-reperfusion injury ( Pan et al, 2020 ). Our results showed that transcription factors bind to the promoter of miRNA and induce miRNA express, so as to form a negative feedback loop with TF and maintain the stability of their expression level.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 is suppressed when miR-210 is overexpressed. miR-210 knockout mice showed higher expression of SMAD4 and lower inflammatory markers and apoptosis [43]. Upon IRI, the miR-210 knockout mice had significantly lower ALT and AST levels in addition to lower TNF-α, IL-6, and IL-1β when compared to the wild-type mice [43].…”
Section: Mirna-370mentioning
confidence: 99%
“…miRNA-210 miR-210 was upregulated, leading to an increase in hepatocyte apoptosis during hepatic IRI [43]. miR-210 targets SMAD4 in the hypoxia pathway [43]. SMAD4 is suppressed when miR-210 is overexpressed.…”
Section: Mirna-370mentioning
confidence: 99%
See 2 more Smart Citations